2019
DOI: 10.1128/mbio.00311-19
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Phytoestrogen-Associated Infertility in Southern White Rhinoceros

Abstract: With recent poaching of southern white rhinoceros (SWR [Ceratotherium simum simum]) reaching record levels, the need for a robust assurance population is urgent. However, the global captive SWR population is not currently self-sustaining due to the reproductive failure of captive-born females. Dietary phytoestrogens have been proposed to play a role in this phenomenon, and recent work has demonstrated a negative relationship between diet estrogenicity and fertility of captive-born female SWR. To further examin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 52 publications
(77 reference statements)
2
42
1
Order By: Relevance
“…Previous large wildlife studies that included a few rhinoceros samples demonstrated that host phylogeny and diet influenced bacterial diversity, and the most abundant phyla in most mammals were Firmicutes and Bacteroidetes (Ley et al, 2008; Youngblut et al, 2019). Therefore, the dominance of these two phyla members in the gut microbiota of rhinoceroses across several North American zoos was expected and in accordance with reports of rhinoceros microbiome in China (Bian et al, 2013), Europe (Antwis et al, 2019), San Diego (Williams et al, 2019), South Africa and Texas (Gibson et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Previous large wildlife studies that included a few rhinoceros samples demonstrated that host phylogeny and diet influenced bacterial diversity, and the most abundant phyla in most mammals were Firmicutes and Bacteroidetes (Ley et al, 2008; Youngblut et al, 2019). Therefore, the dominance of these two phyla members in the gut microbiota of rhinoceroses across several North American zoos was expected and in accordance with reports of rhinoceros microbiome in China (Bian et al, 2013), Europe (Antwis et al, 2019), San Diego (Williams et al, 2019), South Africa and Texas (Gibson et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, the Sumatran rhinoceros metabolome was more closely associated with those of the GOH rhinoceros and white rhinoceros. Williams et al (2019) also reported similar metabolite composition between GOH and white rhinoceroses despite differences in gut microbial composition.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The effect of soy intake on microbiota composition and diversity has been studied in other animal models, such as porcine models [61,63] and the Southern white rhinoceros [62]. Yeruva et al (2016) [63] determined the influence of diet on the development of the immune system in neonates, using a porcine model.…”
Section: Phytoestrogensmentioning
confidence: 99%
“…A recent study with Southern white rhinoceros (SWR, Ceratotherium simum simum) suggested that dietary phytoestrogens might transform the gut microbiota composition, which may be another mechanism resulting in increased infertility in captive populations fed a diet enriched with such compounds (71). The bacterial profiles of SWR were compared to that of the greater one-horned rhinoceros (GOHR [Rhinoceros unicornis]), who consume a similar phytoestrogen rich diet but show high levels of fertility in captivity.…”
Section: Effects Of Phytoestrogens On the Gut Microbiomementioning
confidence: 99%